High-strength waterproof uvioresistant fabric and preparation method thereof
Through the silane modification and in-situ polymerization technology of nanotitanium dioxide, combined with the blending method of polyester fiber and ultra-high molecular weight polyethylene fiber, the problem of insufficient fabric strength, waterproof and UV resistance is solved, and the multiple functional effects of high strength, waterproof and UV resistance are achieved.
Patent Information
- Application Number
- CN202510037875.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-01-10
- Publication Date
- 2025-03-28
AI Technical Summary
Existing fabrics have shortcomings in strength, waterproof and UV resistance, making it difficult to meet the multiple functional requirements of high strength, waterproof and UV resistance.
By ultrasonic dispersing nanotitanium dioxide into anhydrous ethanol and undergoing silane modification treatment, in situ polymerization was carried out in situ by combining 4-propyleneoxy-2-hydroxybenzophenone as an ultraviolet absorber to form anti-UV modified titanium dioxide. It is then blended with polyester fiber and ultra-high molecular weight polyethylene fiber, a base cloth is woven and impregnated to form a high-strength waterproof and UV-resistant fabric.
The fabric is achieved with high strength, excellent waterproofing and significant UV resistance. At the same time, the stability of the functional components is maintained through chemical grafting technology, avoiding the decline in functional performance after multiple washes.
Smart Images

Figure BDA0005236048990000101
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of functional fabrics, in particular to a high-strength waterproof and anti-ultraviolet fabric and a preparation method thereof. Background Art
[0002] With the rapid development of science and technology and economy, people's living standards have been greatly improved, and the pursuit of quality of life has been continuously improved. The requirements for clothing fabrics are not limited to the original functions of clothing such as shelter, warmth, and protection, and more and more functional requirements have been put forward. In recent years, with the rise of outdoor sports and people's pursuit of quality of life, the requirements for fabrics have become higher and higher. Not only are fabrics required to have high strength and wear resistance, but they are also required to have multiple functions such as waterproof, UV resistance, breathable and moisture permeable.
[0003] Chinese patent application CN103790024A discloses a high-density waterproof coating fabric, which includes a base fabric layer and at least one coating layer. By coating a slurry coating composed of a modified polyurethane resin, a silane coupling agent, etc. on the base fabric layer, a coated fabric with good waterproof effect and stable coating performance is obtained, but the anti-ultraviolet effect and strength of the fabric obtained by this method are average. Chinese patent application CN109371686A discloses an anti-ultraviolet coating agent for down jacket fabrics, whose raw materials include: water-based polycarbonate polyurethane, polyketone resin, modified graphene ultraviolet absorber, thickener, defoamer, leveling agent, dispersant, film-forming aid, and the anti-ultraviolet coating agent can effectively improve the anti-ultraviolet performance of down jacket fabrics, but the waterproof performance is average.
[0004] Therefore, it is of great practical significance to develop fabrics with comprehensive properties of waterproofness and UV resistance. Summary of the invention
[0005] 1. Technical issues to be resolved
[0006] In view of the deficiencies in the prior art, the present invention provides a high-strength waterproof and anti-ultraviolet fabric and a preparation method thereof, which solves the problems of low fabric strength, poor waterproofness and anti-ultraviolet effects.
[0007] (II) Technical solution
[0008] In order to achieve the above object, the present invention discloses a method for preparing a high-strength waterproof anti-ultraviolet fabric, comprising the following steps:
[0009] S1. Ultrasonic dispersion of nano titanium dioxide in anhydrous ethanol, after uniform dispersion, adding γ-methacryloxypropyltrimethoxysilane and triethoxy-1H,1H,2H,2H-tridecafluoro-n-octylsilane, stirring and mixing, reacting, cooling, filtering, washing with anhydrous ethanol, and drying at 80° C. for 12 h to obtain silane-modified titanium dioxide;
[0010] S2, ultrasonically dispersing the silane-modified titanium dioxide in anhydrous ethanol, adding 4-propyleneoxy-2-hydroxybenzophenone and an initiator after uniform dispersion, mixing, reacting, filtering after the reaction, washing with deionized water and ethanol, and vacuum drying at 60° C. for 12 h to obtain UV-resistant modified titanium dioxide;
[0011] S3, stirring and mixing deionized water, anti-ultraviolet modified titanium dioxide, softener, antistatic agent, and polyurethane resin to obtain a finishing agent;
[0012] S4. Blend polyester fiber and ultra-high molecular weight polyethylene fiber to obtain warp yarn and weft yarn, weave to obtain base fabric, impregnate the base fabric into a finishing agent, perform an impregnation treatment, the impregnation temperature is 60-70°C, the impregnation time is 2-3h, after the impregnation treatment, dry at 80-90°C for 1-2h, wash, and then dry at 75-85°C for 2-3h to obtain a high-strength waterproof and UV-resistant fabric.
[0013] Preferably, the mass ratio of nano-titanium dioxide, anhydrous ethanol, γ-methacryloxypropyltrimethoxysilane and triethoxy-1H,1H,2H,2H-tridecafluorooctylsilane in S1 is 100:(3500-4200):(45-75):(30-52).
[0014] Preferably, the reaction temperature in S1 is 60-70° C., and the reaction time is 9-15 h.
[0015] Preferably, the mass ratio of silane-modified titanium dioxide, anhydrous ethanol, 4-propyleneoxy-2-hydroxybenzophenone and initiator in S2 is 100:(1800-2500):(38-55):(0.3-0.5).
[0016] Preferably, the reaction temperature in S2 is 55-65° C., and the reaction time is 5-8 h.
[0017] Preferably, the initiator in S2 is benzoyl peroxide.
[0018] Preferably, the mass ratio of deionized water, anti-ultraviolet modified titanium dioxide, softener, antistatic agent and polyurethane resin in S3 is 100:(4-9):(3-5):(0.5-0.8):(1-2).
[0019] Preferably, the softener in S3 is bis-amino-terminated polydimethylsiloxane.
[0020] Preferably, the antistatic agent in S3 is octadecyl dihydroxyethyl methyl ammonium bromide.
[0021] Preferably, the mass ratio of the polyester fiber to the ultra-high molecular weight polyethylene fiber in S4 is 100:(55-70).
[0022] Preferably, the weight of the base fabric in S4 is 205-250 g / m 2 .
[0023] Preferably, the mass ratio of warp yarn to weft yarn in the base fabric in S4 is 100:(80-88).
[0024] Preferably, the mass ratio of the base fabric to the finishing agent in S4 is 100:(680-900).
[0025] A high-strength waterproof anti-ultraviolet fabric prepared by adopting the preparation method of the high-strength waterproof anti-ultraviolet fabric.
[0026] (III) Beneficial technical effects
[0027] In the present invention, γ-methacryloxypropyltrimethoxysilane and triethoxy-1H,1H,2H,2H-tridecafluoro-n-octylsilane are used to modify nano titanium dioxide, alkenyl groups, a large number of fluorine atoms and long-chain alkanes are introduced on the surface of nano titanium dioxide to obtain silane-modified titanium dioxide, and silane-modified titanium dioxide and ultraviolet absorber 4-propyleneoxy-2-hydroxybenzophenone are in situ polymerized under the action of an initiator to obtain anti-ultraviolet modified titanium dioxide. Deionized water, anti-ultraviolet modified titanium dioxide, softener, antistatic agent and polyurethane resin are stirred and mixed uniformly to obtain a finishing agent, polyester fiber and ultrahigh molecular weight polyethylene fiber are used as raw materials, a base fabric is obtained by weaving, and the base fabric is impregnated in the finishing agent to obtain a high-strength waterproof anti-ultraviolet fabric.
[0028] Compared with the prior art, the present invention has the following beneficial effects:
[0029] (1) The nano titanium dioxide particles in the present invention are small. When exposed to ultraviolet rays, they can scatter ultraviolet rays in all directions, reducing the intensity of ultraviolet rays in the irradiation direction. When exposed to light, the electrons on the valence band of the nano titanium dioxide can absorb ultraviolet rays and transition to the conduction band, which has a strong ultraviolet absorption ability, giving the fabric excellent anti-ultraviolet performance and protecting the skin from ultraviolet rays. At the same time, nano titanium dioxide has excellent mechanical properties and wear resistance, which can effectively improve the mechanical properties of the fabric. After chemical modification, the agglomeration of nano titanium dioxide is effectively avoided, and it can be evenly dispersed on the base fabric, with excellent dispersibility and stability. Benzophenone ultraviolet absorbers can absorb high-energy ultraviolet light, convert light energy into heat energy for release, or convert it into other harmless energy forms for release, playing a role in ultraviolet absorption. The synergistic effect of the two further enhances the anti-ultraviolet ability of the fabric. At the same time, the fabric will be washed many times during use, and through chemical grafting, the precipitation of functional components is effectively avoided, maintaining excellent anti-ultraviolet performance.
[0030] (2) The polyester fiber and ultra-high molecular weight polyethylene fiber used in the present invention have the characteristics of high strength, stable chemical structure and are not easy to be damaged. The polyester fiber has good toughness, is not easy to be damaged, has good elasticity and good heat resistance, and the ultra-high molecular weight polyethylene fiber has excellent mechanical properties and anti-ultraviolet radiation performance. The prepared base fabric has excellent comprehensive performance. The added nano-titanium dioxide plays a role of bonding the substrate after being surface-modified by silane, effectively avoiding the agglomeration of nano-titanium dioxide, making the surface hydrophobic, and improving the waterproof ability. Fluorine atoms have strong electronegativity and a small atomic radius, higher chemical stability, reduced surface energy, better water-repellent, oil-repellent and self-cleaning properties, and introduce a large number of alkyl long chains, which can greatly improve the flexibility of the matrix. Furthermore, the special chemical bonds and cross-linked structures formed by the introduced active groups such as fluorine atoms and hydroxyl groups help to enhance the bonding force between the finishing agent and the substrate and improve the comprehensive performance of the fabric. Polyurethane resin is a high-strength, high-durability waterproof material. Ionic and non-ionic polyurethanes are generated by the reaction of isocyanate in the material with water, forming a non-porous, continuous waterproof layer that can effectively prevent moisture from penetrating into the base fabric, thereby achieving a waterproof effect. Polyurethane resin and silane-modified nano-titanium dioxide work together to form a uniform mechanical network on the surface. The two complement each other, have good dispersibility, good density and adhesion, and have excellent durability and waterproof properties. DETAILED DESCRIPTION
[0031] The technical solutions in the embodiments of the present invention will be clearly and completely described below in conjunction with the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, rather than all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without making creative work are within the scope of protection of the present invention.
[0032] Example 1
[0033] A method for preparing a high-strength waterproof and UV-resistant fabric comprises the following steps:
[0034] S1. Ultrasonic dispersion of nano titanium dioxide in anhydrous ethanol, after uniform dispersion, adding γ-methacryloxypropyl trimethoxysilane and triethoxy-1H,1H,2H,2H-tridecafluoro-n-octylsilane, wherein the mass ratio of nano titanium dioxide, anhydrous ethanol, γ-methacryloxypropyl trimethoxysilane and triethoxy-1H,1H,2H,2H-tridecafluoro-n-octylsilane is 100:3500:45:30, stirring and mixing, reacting at 60° C. for 15 hours, cooling, filtering, washing with anhydrous ethanol, and drying at 80° C. for 12 hours to obtain silane-modified titanium dioxide;
[0035] S2, ultrasonically dispersing silane-modified titanium dioxide in anhydrous ethanol, after uniform dispersion, adding 4-propyleneoxy-2-hydroxybenzophenone and initiator benzoyl peroxide, wherein the mass ratio of silane-modified titanium dioxide, anhydrous ethanol, 4-propyleneoxy-2-hydroxybenzophenone and initiator benzoyl peroxide is 100:1800:38:0.3, mixing, reacting at 55°C for 8 hours, after the reaction is completed, filtering, washing with deionized water and ethanol, and vacuum drying at 60°C for 12 hours to obtain UV-resistant modified titanium dioxide;
[0036] S3, mixing deionized water, anti-ultraviolet modified titanium dioxide, softener bisamino-terminated polydimethylsiloxane, antistatic agent octadecyl dihydroxyethyl methyl ammonium bromide, and polyurethane resin in a mass ratio of 100:4:3:0.5:1, and obtaining a finishing agent;
[0037] S4, blending polyester fiber and ultra-high molecular weight polyethylene fiber in a mass ratio of 100:55 to obtain warp yarn and weft yarn, and weaving to obtain a base fabric, wherein the mass ratio of the warp yarn to the weft yarn in the base fabric is 100:80, and the gram weight of the base fabric is 205g / m 2 The base fabric is immersed in the finishing agent, the mass ratio of the base fabric to the finishing agent is 100:680, and the immersion treatment is performed. The immersion temperature is 60°C, the immersion time is 3h, and after the immersion treatment, it is dried at 80°C for 2h, washed, and then dried at 75°C for 3h to obtain a high-strength waterproof and UV-resistant fabric.
[0038] Example 2
[0039] A method for preparing a high-strength waterproof and UV-resistant fabric comprises the following steps:
[0040] S1. Ultrasonic dispersion of nano titanium dioxide in anhydrous ethanol, after uniform dispersion, adding γ-methacryloxypropyl trimethoxysilane and triethoxy-1H,1H,2H,2H-tridecafluoro-n-octylsilane, wherein the mass ratio of nano titanium dioxide, anhydrous ethanol, γ-methacryloxypropyl trimethoxysilane and triethoxy-1H,1H,2H,2H-tridecafluoro-n-octylsilane is 100:4000:65:46, stirring and mixing, reacting at 65° C. for 14 hours, cooling, filtering, washing with anhydrous ethanol, and drying at 80° C. for 12 hours to obtain silane-modified titanium dioxide;
[0041] S2, ultrasonically dispersing silane-modified titanium dioxide in anhydrous ethanol, after uniform dispersion, adding 4-propyleneoxy-2-hydroxybenzophenone and initiator benzoyl peroxide, wherein the mass ratio of silane-modified titanium dioxide, anhydrous ethanol, 4-propyleneoxy-2-hydroxybenzophenone and initiator benzoyl peroxide is 100:2200:50:0.4, mixing, reacting at 60°C for 7 hours, filtering after the reaction, washing with deionized water and ethanol, and vacuum drying at 60°C for 12 hours to obtain UV-resistant modified titanium dioxide;
[0042] S3, mixing deionized water, anti-ultraviolet modified titanium dioxide, softener bisamino-terminated polydimethylsiloxane, antistatic agent octadecyl dihydroxyethyl methyl ammonium bromide, and polyurethane resin in a mass ratio of 100:6:3.5:0.6:1.2, and obtaining a finishing agent;
[0043] S4, blending polyester fiber and ultra-high molecular weight polyethylene fiber in a mass ratio of 100:60 to obtain warp yarn and weft yarn, and weaving to obtain a base fabric, wherein the mass ratio of the warp yarn to the weft yarn in the base fabric is 100:82, and the gram weight of the base fabric is 224g / m 2 The base fabric is immersed in the finishing agent, the mass ratio of the base fabric to the finishing agent is 100:750, and the immersion treatment is performed. The immersion temperature is 65°C, and the immersion time is 2.5 hours. After the immersion treatment, it is dried at 85°C for 1.5 hours, washed, and then dried at 80°C for 2.5 hours to obtain a high-strength waterproof and UV-resistant fabric.
[0044] Example 3
[0045] A method for preparing a high-strength waterproof and UV-resistant fabric comprises the following steps:
[0046] S1. Deionized water, anti-ultraviolet modified titanium dioxide, softener diamino-terminated polydimethylsiloxane, antistatic agent octadecyl dihydroxyethyl methyl ammonium bromide, and polyurethane resin in a mass ratio of 100:7:4:0.7:1.5 are stirred and mixed uniformly to obtain a finishing agent;
[0047] S2. Blending polyester fiber and ultra-high molecular weight polyethylene fiber in a mass ratio of 100:65 to obtain warp yarn and weft yarn, and weaving to obtain a base fabric, wherein the mass ratio of the warp yarn to the weft yarn in the base fabric is 100:86, and the gram weight of the base fabric is 245 g / m 2 The base fabric is immersed in the finishing agent, the mass ratio of the base fabric to the finishing agent is 100:850, and the immersion treatment is performed. The immersion temperature is 65°C, and the immersion time is 2.5 hours. After the immersion treatment, it is dried at 85°C for 1.5 hours, washed, and then dried at 80°C for 2.5 hours to obtain a high-strength waterproof and UV-resistant fabric.
[0048] The preparation method of the anti-ultraviolet modified titanium dioxide is the same as the preparation method of the anti-ultraviolet modified titanium dioxide in Example 2.
[0049] Example 4
[0050] A method for preparing a high-strength waterproof and UV-resistant fabric comprises the following steps:
[0051] S1. Ultrasonic dispersion of nano titanium dioxide in anhydrous ethanol, after uniform dispersion, add γ-methacryloxypropyl trimethoxysilane and triethoxy-1H,1H,2H,2H-tridecafluoro-n-octylsilane, wherein the mass ratio of nano titanium dioxide, anhydrous ethanol, γ-methacryloxypropyl trimethoxysilane and triethoxy-1H,1H,2H,2H-tridecafluoro-n-octylsilane is 100:4200:75:52, stir and mix, react at 70°C for 9 hours, cool, filter, wash with anhydrous ethanol, and dry at 80°C for 12 hours to obtain silane-modified titanium dioxide;
[0052] S2, ultrasonically dispersing silane-modified titanium dioxide in anhydrous ethanol, after uniform dispersion, adding 4-propyleneoxy-2-hydroxybenzophenone and initiator benzoyl peroxide, wherein the mass ratio of silane-modified titanium dioxide, anhydrous ethanol, 4-propyleneoxy-2-hydroxybenzophenone and initiator benzoyl peroxide is 100:2500:55:0.5, mixing, reacting at 65°C for 5 hours, after the reaction is completed, filtering, washing with deionized water and ethanol, and vacuum drying at 60°C for 12 hours to obtain UV-resistant modified titanium dioxide;
[0053] S3, mixing deionized water, anti-ultraviolet modified titanium dioxide, softener bisamino-terminated polydimethylsiloxane, antistatic agent octadecyl dihydroxyethyl methyl ammonium bromide, and polyurethane resin in a mass ratio of 100:9:5:0.8:2, and obtaining a finishing agent;
[0054] S4, blending polyester fiber and ultra-high molecular weight polyethylene fiber in a mass ratio of 100:70 to obtain warp yarn and weft yarn, and weaving to obtain a base fabric, wherein the mass ratio of the warp yarn to the weft yarn in the base fabric is 100:88, and the gram weight of the base fabric is 250g / m 2 The base fabric is immersed in the finishing agent, the mass ratio of the base fabric to the finishing agent is 100:900, and the immersion treatment is performed. The immersion temperature is 70°C, the immersion time is 2h, and after the immersion treatment, it is dried at 90°C for 1h, washed, and then dried at 85°C for 2h to obtain a high-strength waterproof and UV-resistant fabric.
[0055] Comparative Example 1
[0056] A method for preparing a functional fabric comprises the following steps:
[0057] S1. Ultrasonic dispersion of nano titanium dioxide in anhydrous ethanol, after uniform dispersion, adding γ-methacryloxypropyl trimethoxysilane and triethoxy-1H,1H,2H,2H-tridecafluoro-n-octylsilane, wherein the mass ratio of nano titanium dioxide, anhydrous ethanol, γ-methacryloxypropyl trimethoxysilane and triethoxy-1H,1H,2H,2H-tridecafluoro-n-octylsilane is 100:4000:65:46, stirring and mixing, reacting at 65° C. for 14 hours, cooling, filtering, washing with anhydrous ethanol, and drying at 80° C. for 12 hours to obtain silane-modified titanium dioxide;
[0058] S2, deionized water, silane-modified titanium dioxide, 4-propyleneoxy-2-hydroxybenzophenone, softener bisamino-terminated polydimethylsiloxane, antistatic agent octadecyl dihydroxyethyl methyl ammonium bromide, and polyurethane resin in a mass ratio of 100:4.7:2.3:4:0.7:1.5 are stirred and mixed uniformly to obtain a finishing agent;
[0059] S3, blending polyester fiber and ultra-high molecular weight polyethylene fiber in a mass ratio of 100:65 to obtain warp yarn and weft yarn, and weaving to obtain a base fabric, wherein the mass ratio of the warp yarn to the weft yarn in the base fabric is 100:86, and the gram weight of the base fabric is 245g / m 2 The base fabric is immersed in the finishing agent, the mass ratio of the base fabric to the finishing agent is 100:850, and the immersion treatment is performed. The immersion temperature is 65°C, the immersion time is 2.5 hours, and after the immersion treatment, it is dried at 85°C for 1.5 hours, washed, and then dried at 80°C for 2.5 hours to obtain a functional fabric.
[0060] Comparative Example 2
[0061] A method for preparing a functional fabric comprises the following steps:
[0062] S1. Deionized water, nano titanium dioxide, 4-propyleneoxy-2-hydroxybenzophenone, softener bisamino-terminated polydimethylsiloxane, antistatic agent octadecyl dihydroxyethyl methyl ammonium bromide, and polyurethane resin in a mass ratio of 100:4.7:2.3:4:0.7:1.5 are stirred and mixed to obtain a finishing agent;
[0063] S2. Blending polyester fiber and ultra-high molecular weight polyethylene fiber in a mass ratio of 100:65 to obtain warp yarn and weft yarn, and weaving to obtain a base fabric, wherein the mass ratio of the warp yarn to the weft yarn in the base fabric is 100:86, and the gram weight of the base fabric is 245 g / m 2 The base fabric is immersed in the finishing agent, the mass ratio of the base fabric to the finishing agent is 100:850, and the immersion treatment is performed. The immersion temperature is 65°C, the immersion time is 2.5 hours, and after the immersion treatment, it is dried at 85°C for 1.5 hours, washed, and then dried at 80°C for 2.5 hours to obtain a functional fabric.
[0064] The nano-titanium dioxide used in the embodiments and comparative examples was purchased from Xuancheng Jingrui New Materials Co., Ltd., model JR05, with an average particle size of 5 nm; the polyurethane resin is HDA-5040 high solid adhesive polyurethane resin; the ultra-high molecular weight polyethylene fiber has a linear density of 1.21-1.35 dtex and a length of 51-60 mm; the polyester fiber was purchased from Jiangsu Sanlian New Materials Co., Ltd., with a fineness of 50D / 144F; other undisclosed reagents are all commercially available.
[0065] Corresponding tests were performed on the fabrics prepared in Examples 1-4 and Comparative Examples 1-2. The test methods and test results are as follows:
[0066] (1) Waterproof performance test: The water pressure resistance test adopts JISL1092B standard. The samples are tested by a water pressure tester. Each sample is tested 5 times and the average value is taken.
[0067] (2) Anti-ultraviolet performance test: The national standard for the test is GB / T 18830-2009 Evaluation of the anti-ultraviolet performance of textiles. The samples were tested using the UV-Vis spectrometer Lambda35 (UV-Vis). The sample size was cut to 5 mm × 5 mm. The scanning range of the wavelength was set to 200-400 nm, and the scanning wavelength interval was 1 nm. Each group of samples had 20 samples and the average value was taken.
[0068] (3) Fabric strength test: The test standard is GB / T 3923.1-2013 "Tensile properties of textile fabrics Part I: Test of breaking strength and breaking elongation - Strip method". The tensile strength of the sample is tested using a YG(B)026H fabric strength tester. The test is repeated 5 times and the average value is taken.
[0069] The above test results are shown in Table 1:
[0070] Table 1
[0071]
[0072] According to the test results in Table 1, it can be seen that the corresponding fabrics in Examples 1-4 have excellent waterproof performance, anti-ultraviolet performance and mechanical strength. The water pressure resistance value of the fabric corresponding to Example 3 can reach 8358mmH2O, the ultraviolet protection factor can reach 99.2, and the strength value is 646.0N. In Comparative Example 1, no ultraviolet absorber was introduced on the surface of silane-modified titanium dioxide, and 4-propyleneoxy-2-hydroxybenzophenone was directly added, the dispersibility became worse, and the anti-ultraviolet effect, waterproof performance and strength all decreased. In Comparative Example 2, no modification was made to nano titanium dioxide, and the dispersibility and compatibility between the finishing agent and the base fabric were greatly reduced, and the waterproof performance was greatly reduced. Nano titanium dioxide and 4-propyleneoxy-2-hydroxybenzophenone were directly added, and the anti-ultraviolet performance was reduced, and the strength was 582.5N.
[0073] Although the embodiments of the present invention have been shown and described, it will be understood by those skilled in the art that various changes, modifications, substitutions and variations may be made to the embodiments without departing from the principles and spirit of the present invention, and that all equivalent changes and improvements made within the scope of the present invention should still fall within the scope of the present invention.
Claims
1. A method for preparing a high-strength waterproof and UV-resistant fabric, characterized in that: The steps include: S1. Ultrasonic dispersion of nano titanium dioxide in anhydrous ethanol, after uniform dispersion, adding γ-methacryloxypropyltrimethoxysilane and triethoxy-1H,1H,2H,2H-tridecafluoro-n-octylsilane, stirring and mixing, reacting, cooling, filtering, washing, and drying at 80° C. for 12 h to obtain silane-modified titanium dioxide; S2, ultrasonically dispersing the silane-modified titanium dioxide in anhydrous ethanol, adding 4-propyleneoxy-2-hydroxybenzophenone and an initiator after the dispersion is uniform, mixing, reacting, filtering, washing, and vacuum drying at 60° C. for 12 h to obtain UV-resistant modified titanium dioxide; S3, stirring and mixing deionized water, anti-ultraviolet modified titanium dioxide, softener, antistatic agent, and polyurethane resin to obtain a finishing agent; S4. Blend polyester fiber and ultra-high molecular weight polyethylene fiber to obtain warp yarn and weft yarn, weave to obtain base fabric, impregnate the base fabric into a finishing agent, perform an impregnation treatment, the impregnation temperature is 60-70°C, the impregnation time is 2-3h, after the impregnation treatment, dry at 80-90°C for 1-2h, wash, and then dry at 75-85°C for 2-3h to obtain a high-strength waterproof and UV-resistant fabric.
2. The method for preparing a high-strength waterproof anti-ultraviolet fabric according to claim 1, characterized in that: The mass ratio of nano titanium dioxide, anhydrous ethanol, γ-methacryloxypropyltrimethoxysilane and triethoxy-1H,1H,2H,2H-tridecafluoro-n-octylsilane in S1 is 100:(3500-4200):(45-75):(30-52).
3. The method for preparing a high-strength waterproof and UV-resistant fabric according to claim 1, characterized in that: The reaction temperature in S1 is 60-70°C, and the reaction time is 9-15h.
4. The method for preparing a high-strength waterproof anti-ultraviolet fabric according to claim 1, characterized in that: The mass ratio of silane-modified titanium dioxide, anhydrous ethanol, 4-propyleneoxy-2-hydroxybenzophenone and initiator in S2 is 100:(1800-2500):(38-55):(0.3-0.5), the reaction temperature is 55-65° C., and the reaction time is 5-8 h.
5. The method for preparing a high-strength waterproof and UV-resistant fabric according to claim 1, characterized in that: The initiator in S2 is benzoyl peroxide.
6. The method for preparing a high-strength waterproof anti-ultraviolet fabric according to claim 1, characterized in that: The mass ratio of deionized water, anti-ultraviolet modified titanium dioxide, softener, antistatic agent and polyurethane resin in S3 is 100:(4-9):(3-5):(0.5-0.8):(1-2).
7. The method for preparing a high-strength waterproof and UV-resistant fabric according to claim 1, characterized in that: The softener in S3 is bisamino-terminated polydimethylsiloxane, and the antistatic agent is octadecyl dihydroxyethyl methyl ammonium bromide.
8. The method for preparing a high-strength waterproof anti-ultraviolet fabric according to claim 1, characterized in that: The mass ratio of polyester fiber to ultra-high molecular weight polyethylene fiber in S4 is 100:(55-70), and the gram weight of the base fabric is 205-250g / m 2 The mass ratio of warp yarn to weft yarn in the base fabric is 100:(80-88).
9. The method for preparing a high-strength waterproof anti-ultraviolet fabric according to claim 1, characterized in that: The mass ratio of the base fabric to the finishing agent in S4 is 100:(680-900).
10. A high-strength waterproof anti-ultraviolet fabric prepared by the method for preparing a high-strength waterproof anti-ultraviolet fabric as described in any one of claims 1 to 9.
Citation Information
Patent Citations
High-density waterproof coated fabric
CN103790024A
Anti-ultraviolet coating agent for down jacket fabric
CN109371686A
Cited By
Wear-resistant anti-aging polyurethane resin and preparation method thereof
CN120059121A
Anti-aging resin material and preparation method thereof
CN121108645A
Anti-aging resin material and method for preparing the same
CN121108645B